Voluntary Disclosure on Ownership Structure and Company Characteristics Perspective - Inna Nurjannah; Indriyana Puspitosari (Profesional Muda Cendekia Publishing, 2020)
According to agency theory, voluntary disclosure can be used as a way to reduce agency costs arising from agency problems. This voluntary disclosure is considered as a way to control agents. Voluntary disclosure is a form of providing information from the company to its stakeholders in addition to mandatory disclosure. Voluntary disclosure has benefits for both managers and shareholders and stakeholders. This study aims to investigate the effect of managerial ownership, foreign ownership, institutional ownership, company size and company age on the extent of voluntary disclosure made by the company. By using 324 observations of companies listed on the Indonesia Stock Exchange in 2017-2018 the results of the Random effect models state that there is a positive influence between company size and company age. then managerial ownership and voluntary disclosure have a negative influence. Institutional ownership and foreign ownership have no influence on voluntary disclosure.